Image device identification and identity privacy protection method via integration of homomorphic encryption and PRNU fingerprints - ZHANG Pinchang; SHEN Yuanzhang; FAN Weibei; DONG Zhenjiang; SHEN Yulong; JIANG Xiaohong; XIAO Fu (Tongxin xuebao)
To address the challenges of device spoofing and identity leakage in image acquisition systems within industrial Internet environments, a secure and robust image device identification method was proposed that integrated homomorphic encryption and physical-layer fingerprinting. Specifically, photo-response non-uniformity (PRNU) fingerprints, which characterized intrinsic sensor-level features, were employed as unique device identifiers. A blind watermarking scheme based on discrete cosine transform (DCT) and singular value decomposition (SVD) was incorporated to establish a robust mapping between PRNU fingerprints and embedded watermarks, ensuring traceable identification even under tampering attacks. Furthermore, an ElGamal-based homomorphic encryption mechanism was designed to perform similarity matching and recognition in the encrypted domain, effectively preserving the privacy of device fingerprints and noise residuals. Experimental results demonstrate that the proposed method significantly enhances recognition accuracy, tamper-resilience, and data privacy protection, and it has the feasibility and practicality for deployment in untrusted industrial communication environments.